Uterine molecular changes for non‐invasive embryonic attachment in the marsupials Macropus eugenii (Macropodidae) and Trichosurus vulpecula (Phalangeridae). Issue 10 (7th August 2017) - Laird, Melanie K.; Dargan, Jessica R.; Paterson, Lillian; Murphy, Christopher R.; McAllan, Bronwyn M.; Shaw, Geoff; Renfree, Marilyn B.; Thompson, Michael B.
Abstract : Pregnancy in mammals requires remodeling of the uterus to become receptive to the implanting embryo. Remarkably similar morphological changes to the uterine epithelium occur in both eutherian and marsupial mammals, irrespective of placental type. Nevertheless, molecular differences in uterine remodeling indicate that the marsupial uterus employs maternal defences, including molecular reinforcement of the uterine epithelium, to regulate embryonic invasion. Non‐invasive (epitheliochorial) embryonic attachment in marsupials likely evolved secondarily from invasive attachment, so uterine defences in these species may prevent embryonic invasion. We tested this hypothesis by identifying localization patterns of Talin, a key basal anchoring molecule, in the uterine epithelium during pregnancy in the tammar wallaby ( Macropus eugenii ; Macropodidae) and the brush tail possum ( Trichosurus vulpecula ; Phalangeridae). Embryonic attachment is non‐invasive in both species, yet Talin undergoes a clear distributional change during pregnancy in M. eugenii, including recruitment to the base of the uterine epithelium just before attachment, that closely resembles that of invasive implantation in the marsupial species Sminthopsis crassicaudata . Basal localization occurs throughout pregnancy in T. vulpecula, although, as for M. eugenii, this pattern is most specific prior to attachment. Such molecular reinforcement of the uterine epithelium for non‐invasive embryonic attachment in marsupials supports the hypothesis that less‐invasive and non‐invasive embryonic attachment in marsupials may have evolved via accrual of maternal defences. Recruitment of basal molecules, including Talin, to the uterine epithelium may have played a key role in this transition.